2019
DOI: 10.1186/s12955-019-1238-2
|View full text |Cite
|
Sign up to set email alerts
|

The Latin American version of the internalized stigma of mental illness scale (LA-ISMI): a multicentric validation study from three Latin American countries

Abstract: BackgroundTo date, no data have been available concerning the psychometric characteristics of the Internalized Stigma of Mental Illness scale (ISMI-29) in Latin American countries. The aim of this study was to validate a Latin American version of the ISMI in people with schizophrenia.MethodsThe study included 253 stabilized outpatients with schizophrenia from 3 Mental Health Services in three Latin American countries: Bolivia (N = 83), Chile (N = 85) and Peru (N = 85). We analyzed the psychometric properties u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In this study the mean scores of social withdrawal was moderate (13.44) level. Previous studies reported the importance of the social withdrawal in the phenomenon of stigmatization (Caqueo-Urízar et al, 2019;Gerlinger et al, 2013). Self-stigmatization of caregivers may lead to unhappiness and despair, perceived devaluation, concealment of the illness, withdrawal from social relations, avoidance of the patient, and lack or delay in seeking treatment (Maiocco et al, 2017;Singh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study the mean scores of social withdrawal was moderate (13.44) level. Previous studies reported the importance of the social withdrawal in the phenomenon of stigmatization (Caqueo-Urízar et al, 2019;Gerlinger et al, 2013). Self-stigmatization of caregivers may lead to unhappiness and despair, perceived devaluation, concealment of the illness, withdrawal from social relations, avoidance of the patient, and lack or delay in seeking treatment (Maiocco et al, 2017;Singh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A higher overall score on the ISMI scale indicates more severe internalized stigmatization. The ISMI has been validated for the Chilean context and its internal consistency and retesting are acceptable for the original version [ 38 ]. The original version of the ISMI scale was translated into Spanish by Bengochea-Seco, et al [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…It presents adequate validity and internal consistency, with Cronbach's Alphas that vary from 0.77 to 0.88. 42 Rosenberg self-esteem scale (RSES): the original scale was designed to assess the self-esteem of adolescents, but its use has spread to other populations that include people with SMI. 8,9,43 It is a unidimensional self-report instrument composed of 10 items and presented adequate validity and reliability (=0.754).…”
Section: Description Of Data Collection Techniques and Instrumentsmentioning
confidence: 99%